Effect of Terminal Levy Contribution on Local Original Revenue - Agustyawati, Dwi; Hastuti; Suriadi; Katjina, Husna; Rais, Muhamad (International Journal of Management Progress, 2023)
The study aims to find out: the contribution of the Wamengkoli Wara terminal levy to regional revenue. Quantitative research is the chosen research methodology. Both secondary and primary data are used. Contribution analysis is used in data analysis. The sampling method uses saturated samples over a period of 5 years, or from 2018 to 2022. All data needed to collect data based on research in the form of concepts, definitions, or theories that can be applied to explain the problem to be discussed through this research. The Regional Revenue Office, the Transportation Office, and in this case customers are secondary data sources. The study findings show that: The average contribution of the wamengkoli wara terminal levy to Regional Original Revenue during 2018-2022 is 1.63% This shows that the contribution of the terminal levy is still considered insufficient due to several things such as the COVID-19 pandemic and inter-district rental car/motorbike bus users prefer to raise and drop off passengers outside the terminal. In general, passengers who travel back and forth have private vehicles that are not collectible to the terminal Central Buton Regency is still a new pemekaran area, so the volume of terminal service users is still lacking.